The Effect of Improving Spiritual Quotient and Emotional Quotient on Mental Health in Sya'ban Month at The Pandemic Covid 19 in Jakarta, Indonesia - Kartika, Ika; Saepudin; Setiawati, Yanti Hasbian (Al-Wasathiyah: Journal of Islamic Studies, 2022)
This study focuses on the effect of increasing spiritual quotient and emotional quotient on mental health during the month of Sya'ban during the Covid 19 pandemic. This study aims to determine and analyze the positive effects of the spiritual quotient on mental health in the month of Sya'ban. This research uses quantitative research methods. The sample was determined randomly amounting to 100 people. Data collection tools use instruments that are distributed to research respondents. Data were analyzed using the Path Analysis model, which is to analyze the positive effects of spiritual quotient and mental health. The results of this study indicate that the spiritual quotient has a positive effect on mental health during the month of Sya'ban during the Covid 19 pandemic. To improve mental health, it is necessary to increase intelligence and spirituality as a strategic effort to improve the quality of piety.